(untitled) (Global Journal of Human-Social Science, 2017)
Conflict between Farmers and Herdsmen in the North Central Region of Nigeria is an age long phenomenon which became severe shortly after the transfer of power from country on 29th May 1999. In its current stage, the conflict h as one of the major threats to Nigeria`s national security. This research examined some of the effective strategies that can be adopted in the proper resolution and management of the conflict. It was conducted with the used of both qualitative and quantitative research methodologies.